SEBARAN RUMPON PESISIR PADA DAERAH PENANGKAPAN PURSE SEINE DI PERAIRAN DESA URENG KECAMATAN LEIHITU, KABUPATEN MALUKU TENGAH - Muhidin Syamsuddin; Deni Sarianto; Djalaludin Kemhay; Adnal Yeka (JURNAL PERIKANAN TROPIS, 2021)
The Fish Aggregating Devices (FADs) have been utilized for a long time by the purse seine fishermen in Ureng. This research was aimed at mapping the devices operating by Ureng fishermen and indentifying the dominant captured fish surrounding the set devices. This research was conducted in Lihitu district, Central Maluku Regency. The results showed that there was one large circle that resembled a ball with several groups of five small circles inside. Based on the type, the dominant fish caught around the FADs were mackerel (45 ton), mackerel tuna (25 ton), and skipjack tuna (20 ton). Overall, this study found that the catch using the purse seine in the five FAD groups was dominated by small and medium sized fish. In conclusion, under the potential fishing area for purse saine fishermen in Ureng, if the distance between the FADs is adjusted, fish are not trapped forever in the FADs and can migrate, lay eggs in other areas outside the waters of Ureng.